The Concepts of Naṣ, Ẓāhir, and Mu’awwal in Ushul Fiqh and Their Implications for Drawing Legal Conclusions in Islamic Law - Muhammad Sauqi; Laili Nuzulur Rahmah; Nor Hidayah; Anggun (SETYAKI : Jurnal Studi Keagamaan Islam, 2026)
This study analyzes the concepts of naṣ, ẓāhir, and mu’awwal in ushul fiqh and their implications for Islamic legal deduction (istinbaṭ al-aḥkām). These three concepts are essential for understanding Islamic legal texts, since not all Qur’anic and prophetic texts share the same level of clarity of meaning. The research employs a library research method with an ushul fiqh approach and a descriptive-analytical analysis of classical and contemporary literature. The results show that naṣ is a text whose meaning is entirely clear and admits no other possible meaning; ẓāhir is a text whose meaning is clear yet still allows interpretation (ta’wīl); while mu’awwal is a text whose apparent meaning has been diverted on the basis of stronger supporting evidence. The implications of these three concepts significantly affect the process of legal deduction, especially in determining obligatory, recommended, forbidden, and disliked rulings. A proper understanding of naṣ, ẓāhir, and mu’awwal is therefore crucial for mujtahids in establishing Islamic law.